KEHIDUPAN SOSIAL EKONOMI PETANI KARET NAGARI SIGUNTUR KABUPATEN DHARMASRAYA TAHUN 1994-2011 - Hermantoni, Hermantoni; Kaksim, Kaksim; Kharles, Kharles (Pendidikan Sejarah, 2014)
The rubber plant is a plant on Siguntur Village Sitiung District Dharmasraya, so the rubber is the principal livelihood of the people Siguntur. For the problem is formulated as follows: Social Life Economy Rubber Farmers Siguntur Village Sitiung District Dharmasraya Year 1994-2011. This research includes the study of history with research methods as follows: (1) heuristic, (2) a source of criticism, (3) an interpretation and (4) the stage of writing a thesis result. The results showed that the Socio-Economic Life Rubber Farmers Siguntur Village Sitiung District Dharmasraya 1994 â 2011 has significant development, can be seen from the four indicators: socio-economic life of society Siguntur Village Sitiung District before 1994 including difficult, because the rubber plantations owned by people not using good seed so that the socio-economic condition is not good, average income average Rp 500.000/month. At1994 was beginning with a rubber planted seeds and early 2000 with the rubber crop seeds and social and economic conditions began to improve in the early harvest using rubber seeds accompanied by increased production and the price of rubber farmers followed by the increasing of children who on to higher levels and the increasing able to meet the needs in addition to basic needs. Improved social interaction in the community because people have more leisure time and better economic conditions, which people become more consumer goods to the secondary but no change customs.